\(\left(x-1\right)^2+x.\left(2-x\right)\)
rút gọn biểu thức
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\left(x-3\right)\left(x^2+1-x^2+1\right)=2\left(x-3\right)\)
a: \(\left(x-2y\right)^2+\left(x-\dfrac{1}{2}y\right)\left(x+\dfrac{1}{2}y\right)\)
\(=x^2-4xy+4y^2+x^2-\dfrac{1}{4}y^2\)
\(=2x^2-4xy+\dfrac{15}{4}y^2\)
b: \(\left(x-2\right)^2+\left(x+3\right)^2-2\left(x-1\right)\left(x+1\right)\)
\(=x^2-4x+4+x^2+6x+9-2\left(x^2-1\right)\)
\(=2x^2+2x+13-2x^2+2\)
=2x+15
a) \(=x^2-4xy+4y^2+x^2-\dfrac{1}{4}y^2=2x^2-4xy+\dfrac{15}{4}y^2\)
b) \(=x^2-4x+4+x^2+6x+9-2x^2+2\)
\(=2x+15\)
a: \(\left(2x+1\right)^2+2\left(4x^2-1\right)+\left(2x-1\right)^2\)
\(=\left(2x+1\right)^2+2\left(2x+1\right)\left(2x-1\right)+\left(2x-1\right)^2\)
\(=\left(2x+1+2x-1\right)^2=\left(4x\right)^2=16x^2\)
b: \(\left(x^2-1\right)\left(x+2\right)-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=x^3+2x^2-x-2-x^3+8\)
\(=2x^2-x+6\)
a) \(\left(2x+1\right)^2+2\left(4x^2-1\right)+\left(2x-1\right)^2\)
\(=\left(2x+1\right)^2+2\left(2x+1\right)\left(2x-1\right)+\left(2x-1\right)^2\)
\(=\left[\left(2x+1\right)+\left(2x-1\right)\right]^2\)
\(=\left(2x+1+2x-1\right)^2\)
\(=\left(4x\right)^2\)
\(=16x^2\)
b) \(\left(x^2-1\right)\left(x+2\right)-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=\left(x^3+2x^2-x-2\right)-\left(x^3-8\right)\)
\(=x^3+2x^2-x-2-x^3+8\)
\(=2x^2-x+6\)
a: \(2x\left(2x-1\right)^2-3x\left(x+3\right)\left(x-3\right)-4x\left(x+1\right)^2\)
\(=2x\left(4x^2-4x+1\right)-3x\left(x^2-9\right)-4x\left(x^2+2x+1\right)\)
\(=8x^3-8x^2+2x-3x^3+27x-4x^3-8x^2-4x\)
\(=x^3-16x^2+25x\)
\(=\left(x-1\right)^2-\left(x+2\right)\left[2\left(x-2\right)+3\left(x+2\right)^2\right]\)
\(=x^2-2x+1-\left(x+2\right)\left[2x-4+3\left(x^2+4x+4\right)\right]\)
\(=x^2-2x+1-\left(x+2\right)\left(3x^2+14x+8\right)\)
\(=x^2-2x+1-\left(3x^3+6x^2+14x^2+28x+8x+16\right)\)
\(=-3x^3-21x^2-38x-15\)
\(\left(x+y\right)^2+\left(x-y\right)^2+\left(x-y\right)\left(x+y\right)-3x^2\)
\(=\left(x^2+2xy+y^2\right)+\left(x^2-2xy+y^2\right)+\left(x^2-y^2\right)-3x^2\)
\(=x^2+2xy+y^2+x^2-2xy+y^2+x^2-y^2-3x^2\)
\(=3x^2+y^2-3x^2\)
\(=y^2\)
\(\left(x-1\right)^2+x\left(2-x\right)\)
\(=x^2-2x+1+2x-x^2\)
\(=1\)
học tốt nha~
(x-1)2+x(2-x)
=x2-2x+1+2x-x2
=1
k mk nha